Enhancement of motor-imagery ability via combined action observation and motor-imagery training with proprioceptive neurofeedback. (June 2018) - Ono, Yumie; Wada, Kenya; Kurata, Masaya; Seki, Naoto
Abstract: Varied individual ability to control the sensory-motor rhythms may limit the potential use of motor-imagery (MI) in neurorehabilitation and neuroprosthetics. We employed neurofeedback training of MI under action observation (AO: AOMI) with proprioceptive feedback and examined whether it could enhance MI-induced event-related desynchronization (ERD). Twenty-eight healthy young adults participated in the neurofeedback training. They performed MI while watching a video of hand-squeezing motion from a first-person perspective. Eleven participants received correct proprioceptive feedback of the same hand motion with the video, via an exoskeleton robot attached to their hand, upon their successful generation of ERD. Another nine participants received random feedback. The training lasted for approximately 20 min per day and continued for 6 days within an interval of 2 weeks. MI-ERD power was evaluated separately, without AO, on each experimental day. The MI-ERD power of the participants receiving correct feedback, as opposed to random feedback, was significantly increased after training. An additional experiment in which the remaining eight participants were trained with auditory instead of proprioceptive feedback failed to show statistically significant increase in MI-ERD power. The significant training effect obtained in shorter training time relative to previously proposed methods suggests the superiority of AOMI training and physiologically-congruent proprioceptive feedback to enhance the MI-ERD power. The proposed neurofeedback training could help patients with motor deficits to attain better use of brain-machine interfaces for rehabilitation and/or prosthesis. Highlights: Proprioceptive neurofeedback was employed for motor imagery (MI) training. The feedback was provided with an action video to be imagined upon successful MI. Training outcome was compared with that from pseudo or auditory feedback. Only proprioceptive feedback enhanced MI ability through 6 days of training. The proposed method is useful for MI-related motor learning and rehabilitation.